Remote ischemic preconditioning versus sham-control for prevention of anastomotic leakage after resection for rectal cancer (RIPAL trial): a pilot randomized controlled, triple-blinded monocenter trial : research - Hardt, Julia; Seyfried, Steffen; Brodrecht, Hannah; Khalil, Leila; Büttner, Sylvia; Herrle, Florian; Reißfelder, Christoph; Rahbari, Nuh Nabi (International journal of colorectal disease, 2024)
Purpose Remote ischemic preconditioning (RIPC) reportedly reduces ischemia‒reperfusion injury (IRI) in various organ systems. In addition to tension and technical factors, ischemia is a common cause of anastomotic leakage (AL) after rectal resection. The aim of this pilot study was to investigate the potentially protective effect of RIPC on anastomotic healing and to determine the effect size to facilitate the development of a subsequent confirmatory trial. Materials and methods Fifty-four patients with rectal cancer (RC) who underwent anterior resection were enrolled in this prospectively registered (DRKS0001894) pilot randomized controlled triple-blinded monocenter trial at the Department of Surgery, University Medicine Mannheim, Mannheim, Germany, between 10/12/2019 and 19/06/2022. The primary endpoint was AL within 30 days after surgery. The secondary endpoints were perioperative morbidity and mortality, reintervention, hospital stay, readmission and biomarkers of ischemia‒reperfusion injury (vascular endothelial growth factor, VEGF) and cell death (high mobility group box 1 protein, HMGB1). RIPC was induced through three 10-min cycles of alternating ischemia and reperfusion to the upper extremity. Results Of the 207 patients assessed, 153 were excluded, leaving 54 patients to be randomized to the RIPC or the sham-RIPC arm (27 each per arm). The mean age was 61 years, and the majority of patients were male (37:17 (68.5:31.5%)). Most of the patients underwent surgery after neoadjuvant therapy (29/54 (53.7%)) for adenocarcinoma (52/54 (96.3%)). The primary endpoint, AL, occurred almost equally frequently in both arms (RIPC arm: 4/25 (16%), sham arm: 4/26 (15.4%), p = 1.000). The secondary outcomes were comparable except for a greater rate of reintervention in the sham arm (9 (6-12) vs. 3 (1-5), p = 0.034). The median duration of endoscopic vacuum therapy was shorter in the RIPC arm (10.5 (10-11) vs. 38 (24-39) days, p = 0.083), although the difference was not statistically significant. Conclusion A clinically relevant protective effect of RIPC on anastomotic healing after rectal resection cannot be assumed on the basis of these data.
Online veröffentlicht: 03. Mai 2024
Gesehen am 15.05.2025